Enrichment in Different Health Components of Barley Flour Using Twin-Screw Extrusion Technology to Support Nutritionally Balanced Diets - Punia Bangar, Sneh; Singh Sandhu, Kawaljit; Trif, Monica; Rusu, Alexandru; Pop, Ioana Delia; Kumar, Manoj (Frontiers in Nutrition, 2022)
Due to its good dietary role, barley has attracted a growing amount of interest for the manufacture of functional foods in recent years. In barley, a number of bioactive components, including as phenolic compounds, have been discovered, and barley extrudates could be used to formulate various processed foods, including ready-to-eat cereals, baby, and pet foods and support nutritionally balanced diets. This study was conducted to investigate the effect of extrusion processing on resistant starch (RS), glycemic index (GI), and antioxidant compounds of barley flour. The L* and ΔE values of barley flours decreased significantly (p < 0.05) after extrusion is done at 150 and 180°C. The a* and b* values, however, increased after extrusion. Extrusion increased antioxidant activity (AOA), metal chelating activity (MCA), and ABTS+ scavenging activity, whereas total phenolic content (TPC) and total flavonoids content (TFC) decreased. Barley extrudates at 150 and 180°C showed decreased TPC by 16.4–34.2% and 23.4–38.1%. Moreover, improved RS and reduced GI values were recorded for barley extrudates as compared to barley non-extrudates. Therefore, extrusion of barley could be an alternative to produce pregelatinized barley flour with improved RS low GI values and improved antioxidant potential.